Labor Market Effects of a Work-first Policy for Refugees - Jacob Nielsen Arendt (Global Labor Organization (GLO), 2020)
This study estimates the labor market effects of a work-first policy that aimed at speeding up the labor market integration of refugees. The policy added new requirements for refugees to actively search for jobs and to participate in on-the-job training immediately upon arrival in the host country. The requirements were added to an existing policy that emphasizes human capital investments in language training. The results show that the work-first policy speeded up the entry into regular jobs for males, but that they find work in precarious jobs with few hours. The long-run effects are uncertain since the policy crowds out language investments but raises enrollment in education. The policy had no or very small effects for women, which is partly explained by a lower treatment intensity for women.
Keywords: J61; J64; J68; 330; Refugee; Unemployment; Work-first; Employment Support